The effect of indomethacin on nucleic acids in blood, hemopoietic and lymphoid tissues in continuously irradiated rats - Misúrová, E; Kropácová, K; Chlebovský, O; Pado, D (Neoplasma, 1989)
The effect of indomethacin--a nonsteroid antiinflammatory drug with potential antitumor activity--on the development of radiation-induced changes was followed in blood, bone marrow, spleen, thymus and testes of rats. Indomethacin administered in drinking water (0.7-1.0 mg/kg per day) during a continuous 7-day irradiation with gamma rays (dose rate of 2.055 Gy/day, total accumulated dose of 14.385 Gy) caused a higher and more rapid incorporation of 3H-thymidine into blood DNA, and an increase in blood RNA concentration. The results suggest some stimulation of hemopoiesis recovery by indomethacin treatment in continuously irradiated rats.
Keywords: Bone Marrow; RNA; Spectrophotometry; radioprotektivní látky; Radiation-Protective Agents; Rats, Inbred Strains; krysa rodu Rattus; zvířata; lymfoidní tkáň; časové faktory; indomethacin; DNA; Male; Lymphoid Tissue; dávka záření; Indomethacin; kostní dřeň; spektrofotometrie; Rats; Radiation Dosage; Animals; mužské pohlaví; Time Factors; inbrední kmeny potkanů